COMMUNICATION FOR EMPOWERMENT THROUGH VIRTUAL PHILANTHROPY TO BUILD AN ISLAMIC CREATIVE ECONOMY - Diah Ajeng Purwani (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2022)
The spread of Covid-19 cases in Indonesia has caused a weakening of economic activity, which also impacts economic growth, unemployment, and a decline in income from micro, small and medium enterprises (MSMEs). This study aims to explore the role of the creative economy through virtual philanthropy based on Islamic teachings in helping economic recovery. The type used in this research is qualitative with a phenomenological approach. The data collection technique was primarily done through observation and interviews to strengthen the data. The participants in this study were four communities of micro, small and medium enterprises (MSMEs) engaged in services and one district of empowerment in the region of Yogyakarta, Indonesia, as the subject of research. The results of this study indicate that the presence of a virtual philanthropic community based on Islamic guidelines through social media has an impact on business growth in six essential ways, namely: the movement to buy friends' products, group alms, promote friends' products, buy in cash, usury-free capital assistance, and strengthen networks business. The hope is that this Islamic-based virtual philanthropy can become a driving force of empowerment for small communities.